SOSIALISASI HUKUM WARIS ISLAM DI DESA KARANGPATRI - Adam Firdaus Habibi; Fatimah Dian Eka; Seta Samsiana (An-Nizam, 2023)
As Muslims, especially in Bekasi Regency, heritage in Islamic teachings is one of the many Shari'a of Allah, apart from the obligation to pray, fast during Ramadan, pay zakat, perform the pilgrimage, and other Shari'a. Islamic inheritance law is a rule governing the assets of the deceased to his heirs. This means determining who is the heir, the share of each heir, determining the heir and the heir's share. The implementation of this socialization activity is carried out offline using the lecture method and presenting PPT, with the aim that the community can increase their understanding of Islamic law and to create a sakinah family through Islamic inheritance law. This program has been implemented in Karangpatri village, Pebayuran sub-district, Bekasi Regency which has realized various activities according to plan. First, from observation activities to find the right target and also get permission from the local agency. Second, program planning to gather several groups and create emotional closeness so that activities run smoothly. Third, socialization activities by providing inheritance law material to the public.